From Public Service Media Organisations to De-centralised Public Service for the Media Sector: A Comparative Analysis of Opportunities and Disadvantages - Donders, Karen; Raats, Tim (Javnost-The Public, 2015)
Ideas on plurality and competition in public broadcasting delivery have re-surfaced in discussions on the future of public surface media (PSM) on regular occasions in different geographical settings since the 1980s. This article analyses several of the debates on distributed public service, critically evaluating whether governments across Europe would indeed be “better off” should they choose a distributed and de-centralised model of public service media. The article, firstly, investigates which arguments have been made in order to make the case for a distributed PSM model. On the basis of these insights, a typology of different forms of distributed public service delivery is then developed. Setting out from this typology, policy plans and actual practices of de-centralised PSM are being analysed. Findings in the four case studies (the United Kingdom, Flanders, the Netherlands, and New Zealand) are based on a combination of secondary literature, a qualitative document analysis, desk research and semi-structured expert interviews. The article concludes that distributed public service is as much a normative idea as the centralised public broadcasting project, that distributed public service as a policy solution lacks a clearly defined policy problem and, moreover, that there is, given the variety of media systems, not one distributed model that would fit all.